Improving capacity for advanced training in obstetric surgery: evaluation of a blended learning approach - Helen Allott; Alan Smith; Sarah White; Irene Nyaoke; Ogoti Evans; Michael Oriwo Oduor; Steven Karangau; Sheila Sawe; Nassir Shaaban; Ochola Ephraim; Charles Anawo Ameh (BMC Medical Education)
Abstract Background Significant differences in outcomes for mothers and babies following obstetric surgical interventions between low- and middle-income countries and high-income settings have demonstrated a need for improvements in quality of care and training of obstetric surgical and anaesthetic providers. To address this, a five-day face-to-face training intervention was developed. When roll-out was disrupted by the COVID-19 pandemic, the course was redesigned for delivery by blended learning. Methods This 3-part blended-learning course (part-1: 15 h self-directed online learning, part-2: 13 h facilitated contemporaneous virtual workshops and part-3: 10 h face-to-face delivery), was conducted in Kenya. We assessed the completion rate of part-1 (21 assignments), participation rate in parts 2 and 3, participant satisfaction and change in knowledge and skills. Additionally, we compared the cost of the blended delivery to the 5-day face-to-face delivery, in GB pounds. Results Sixty-five doctors participated in part 1, with 53 completing at least 90% of the assignments. Sixty doctors participated in part 2, and 53 participated in part 3. All participants who completed an evaluation reported (n = 53) that the training was relevant, useful and would lead to changes in their clinical practice. Mean (SD) knowledge score improved from 64% (7%) to 80% (8%) and practical skills from 44% (14%) to 87% (7%). The blended course achieved a cost-saving of £204 per participant compared to the 5-day face-to-face delivery approach. Conclusion We have demonstrated that a blended learning approach to clinical training in a low-resource setting is feasible, acceptable and cost effective. More studies are required to investigate the effectiveness of this approach on health outcomes.